The profile of codon 200 β-tubulin gene of Ascaris lumbricoides L. and Trichuris trichiura L. from infected people in Nangapanda Sub-district, East Nusa Tenggara (Faculty of Medicine Universitas Indonesia, 2018)
Background: The mass administration of anthelmintic such as albendazole is one of the strategies for eliminating soil-transmitted helminth (STH) infection. The widespread and long-term use of anthelmintics can cause resistance. The research on animals shows that factor that the single-nucleotide polymorphism (SNP) codon 200 β-tubulin gene of the worms is one of the factors that can cause the decreased efficacy of anthelmintics. This study aimed to determine the bases of codon 200 in A. lumbricoides and T. trichiura, which infect the people in Nangapanda, East Nusa Tenggara.Methods: The worm samples were obtained from the intestinal helminth-infected patients from Nangapanda Sub-district. The DNA from the worm tissues were isolated, amplificated by polymerase chain reaction (PCR), and sequenced. The sequencing results were aligned to the reference sequence to obtain the codon bases in the 200 β-tubulin gene.Results: TTC constitute the codon bases in the 200 β-tubulin gene found in two A. lumbricoides and one T. trichiura.Conclusion: The SNP codon 200 β-tubulin gene was absent in A. lumbricoides or T. trichiura worms that were examined in this study.